Black gram ( L.) foliage supplementation to crossbred cows: effects on feed intake, nutrient digestibility and milk production - Avijit Dey (Asian-Australasian Journal of Animal Sciences, 2017)
Objective An experiment was conducted to examine the effect of dietary supplementation of dried and ground foliage of black gram (Vigna mungo L.) on feed intake and utilization, and production performance of crossbred lactating cows. Methods Eighteen lactating crossbred (Bos taurus×Bos indicus) cows (body weight 330.93± 10.82 kg) at their second and mid lactation (milk yield 6.77±0.54 kg/d) were randomly divided into three groups of six each in a completely randomized block design. Three supplements were formulated by quantitatively replacing 0, 50, and 100 per cent of dietary wheat bran of concentrate mixture with dried and ground foliage of black gram. The designated supplement was fed to each group with basal diet of rice straw (ad libitum) to meet the requirements for maintenance and milk production. Daily feed intake and milk yield was recorded. A digestion trial was conducted to determine the total tract digestibility of various nutrients. Results The daily feed intake was increased (p<0.05) with the supplementation of black gram foliage. Although the digestibility of dry matter, organic matter, crude protein, and ether extract did not vary (p>0.05), the fibre digestibility was increased (p<0.05), which ultimately improved (p<0.05) the total digestible nutrients content of composite diet. Although, the average milk yield (kg/animal/d) and composition did not differ (p>0.05) among the groups, milk yield was increased by 10 per cent with total replacement of wheat bran in concentrate mixture with of black gram foliage. The economics of milk production calculated as feed cost per kg milk yield (INR 10.61 vs 7.98) was reduced by complete replacement of wheat bran with black gram foliage. Conclusion Black gram foliage could be used as complete replacement for wheat bran in concentrate mixture of dairy cows in formulating least cost ration for economic milk production in small holders’ animal production.